2013
DOI: 10.1158/0008-5472.can-12-3828
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1 Promotes Breast Cancer via Transactivation of the EGF Pathway

Abstract: Chemokines are relevant molecules in shaping the tumor microenvironment, although their contributions to tumorigenesis are not fully understood. We studied the influence of the chemokine CX3CL1/fractalkine in de novo breast cancer formation using HER2/neu transgenic mice. CX3CL1 expression was downmodulated in HER2/neu tumors, yet, paradoxically, adenovirus-mediated CX3CL1 expression in the tumor milieu enhanced mammary tumor numbers in a dose-dependent manner. Increased tumor multiplicity was not a consequenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 48 publications
4
86
0
Order By: Relevance
“…The antitumor effects of CX 3 CL1 are mostly related to attraction of cytotoxic CD8 T lymphocytes and NK cells (40,42,43). However, CX 3 CL1 may also stimulate tumor survival and proliferation, and in breast cancer it promotes tumor progression via trans-activation of the epidermal growth factor pathway (32,52). The dual nature of the CX 3 CR1-CX 3 CL1 axis is an example of the complex interplay between neoplastic cells, the tumor stroma, and infiltrating leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor effects of CX 3 CL1 are mostly related to attraction of cytotoxic CD8 T lymphocytes and NK cells (40,42,43). However, CX 3 CL1 may also stimulate tumor survival and proliferation, and in breast cancer it promotes tumor progression via trans-activation of the epidermal growth factor pathway (32,52). The dual nature of the CX 3 CR1-CX 3 CL1 axis is an example of the complex interplay between neoplastic cells, the tumor stroma, and infiltrating leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…ERK activation, actin polymerization, and chemotaxis assays were performed as described. 36,37 Results CXCR4 C-tail is not the only FLNA binding motif Studies have shown that the CXCR4 C-tail binds to the atypical FLNA repeat 10. 22,38 Sequence analysis predicted a small motif at the CXCR4 C-tail, with charge and secondary structure similar to those identified in CD4 as important for binding to FLNA repeat 10 (supplemental Figure 1A).…”
Section: Methodsmentioning
confidence: 99%
“…Cell populations from tumors were purified as described [58]. Total RNA from total tumor samples or tumor cell fractions was extracted with Tri-Reagent or with the Easy RNA kit (Qiagen, when recovered cells ≤5 × 10 5 ) and used to synthesize the first cDNA strand (High-capacity cDNA Archive Kit, Applied Biosystems) using random primers.…”
Section: Methodsmentioning
confidence: 99%